A global correction to PPMXL proper motions - Vickers, John J.; Röser, Siegfried; Grebel, Eva K. (Arxiv, 2016)
In this paper we notice that extragalactic sources seem to have non-zero proper motions in the PPMXL proper motion catalog. We collect a large, all-sky sample of extragalactic objects and fit their reported PPMXL proper motions to an ensemble of spherical harmonics in magnitude shells. A magnitude dependent proper motion correction is thus constructed. This correction is applied to a set of fundamental radio sources, quasars, and is compared to similar corrections to assess its utility. We publish, along with this paper, code which may be used to correct proper motions in the PPMXL catalog over the full sky which have 2 Micron All Sky Survey photometry.
Gesehen am 07.11.2017